FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI MASYARAKAT DALAM MUSYAWARAH MASYARAKAT DESA DI PUSKESMAS KALIGONDANG KABUPATEN PURBALINGGA - Heryanto Heryanto; Arif Kurniawan; Elviera Gamelia; Arih Diyaning Intiasari (Kesmas Indonesia, 2011)
ABSTRACT Purbalingga District was a pilot project of Desa Siaga Programme in Central Java Province.One of Indicator Desa Siaga Programme was Musyawarah Masyarakat Desa (MMD). The goals of MMD was to find out the helth problem solving and to provide Poliklinik Kesehatan Desa (PKD) with all of potential resources of the village. The Aim of these research was to know the potensialy factor influence MMD in Purbalingga District. Cross sectional survey on village community were conducted in 2008 with a quistionaire. Simple Random Sampling was used to get 96 respondent.There have been three (3) factors that influence positively through MMD Programme : Income, Social Status and Perception to MMD. The suggestion from this research was to held problem solving cycle training for village community and other activity that could be increasing community participation in Purbalingga District. Kata Kunci: rural, participation, community Kesmasindo. Volume 4,(1) Januari 2011, hlm. 1-10